2022
DOI: 10.4049/jimmunol.2100758
|View full text |Cite
|
Sign up to set email alerts
|

One Size Does Not Fit All: Diversifying Immune Function in the Skin

Abstract: Our body’s most outward facing epithelial barrier, the skin, serves as the frontline defense against myriad environmental assailants. To combat these motley threats, the skin has evolved a sophisticated immunological arsenal. In this article, I provide an overview of the skin’s complex architecture and the distinct microniches in which immune cells reside and function. I review burgeoning literature on the synchronized immune, stromal, epithelial, and neuronal cell responses in healthy and inflamed skin. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…For instance, we find that homeostatic effector T cells (T H /T C ) and regulatory T cells (T regs ) cluster with APCs in the perifollicular region around the vasculature. The follicle is home to commensal microbes, is a portal for pathogen and allergen entry, and richly expresses immune modulatory factors ( 33 ). Murine studies have revealed that homeostatic immune surveillance is dependent on follicle-dwelling commensals ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we find that homeostatic effector T cells (T H /T C ) and regulatory T cells (T regs ) cluster with APCs in the perifollicular region around the vasculature. The follicle is home to commensal microbes, is a portal for pathogen and allergen entry, and richly expresses immune modulatory factors ( 33 ). Murine studies have revealed that homeostatic immune surveillance is dependent on follicle-dwelling commensals ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The epidermis is most superficial layer and contains nerves and numerous specialized cells such as keratinocytes, melanocytes, Langerhans cells and Merkel cells ( Orsmond et al, 2021 ). The dermis is located below the epidermis and is rich in fibrous extracellular matrix (ECM), containing fibroblasts and mast cells as well as interspersed resident immune cells like T cells, dendritic cells (DCs) and macrophages which participate in the immune response against pathogen infection ( Orsmond et al, 2021 ; Naik, 2022 ). Moreover, abundant blood vessels and nerves are also found in the dermis.…”
Section: Introductionmentioning
confidence: 99%
“…These cascade processes include cell migration, secretion of cytokines, interleukins, growth factors, and secretion of extracellular matrix proteins, as well as a series of complementary repair processes [ 4 , 5 , 6 ]. Finally, the missing tissue is replenished through the synergistic effects of a series of molecular, biochemical, and cellular processes, which can complete the anatomical reconstruction of the tissue and restore tissue integrity [ 7 , 8 , 9 ]. The wounds can develop into chronic wounds, such as diabetic wounds and infected wounds, which are characterized by hypoxia and infection.…”
Section: Introductionmentioning
confidence: 99%